Processing kamplang Crackers by Addition of Green Spinach Leaft Extract - A. Masuku, Mustamin; Bahri, Syamsul; La Rahman, La Arjun (Agrikan Jurnal Agribisnis Perikanan, 2022)
In general, crackers are consumed as an additional food for side dishes or as a snack. One of the main factors that determine the quality of crackers is the crispness. Spinach is often used as a product, apparently. This research method uses a completely randomized design (CRD) with one factor consisting of 5 treatments and 3 replications in order to obtain 15 experimental units. The treatments consisted of 5 treatments, namely (P0), the addition of 0 ml of spinach leaf extract, (P1), the addition of 50 ml of green spinach leaf extract, (P2), the addition of 100 ml of green spinach leaf extract, (P3), the addition of green spinach leaf extract. 150 ml, and (P4), 200 ml green spinach leaf extract. Parameters observed included physicochemical and organoleptic characteristics, namely water content, covering 8.49-10.49 ash ranging from 2.26-2.52, protein ranging from 9.19-9.59, fat ranging from 0.28-0.65%. and carbohydrates in the range of 78.35-79.21%, the physical properties of swellability ranged from 1.97 to 2.38. Organoleptic namely color ranged from 4.17-4.87, taste ranged from 3.91-4.79, aroma ranged from 4.32-4.56, and texture ranged from 4.17-4.87. When viewed from all treatments ranging from chemical, physical, and organoleptic properties, it turns out that the best value in the P2 treatment is in accordance with the determination of the best ranking value, which is the smallest.